RESTATEMENT AND TAX AGGRESSIVENESS: DOES BUSINESS STRATEGY MATTER? - Sansaloni Butar Butar (AKUNTABILITAS, 2021)
This study examines the effect of business strategy on tax aggressiveness and restatement. Prospectors are more aggressive in choosing accounting policies relative to defenders, thereby increasing the likelihood of restatements. Prospectors are also predicted to be more aggressive in tax planning than defenders. Sample was hand collected from Indonesian public firms in the period of 2014-2018 by using a purposive sampling method. As much as 1630 firm-year observations were gathered during the sample period and subsequently analyzed by employing multiple regressions analysis. A number of control variables are included in the regression model to control for differences in corporate governance system and firm characteristics. The corporate governance variables are Board of Commissioners independence, Audit Committee expertise, and institutional ownership. The firm characteristics variables are firm size, leverage, growth, and profitability. Results show that business strategy has an implication on tax aggressiveness but no effect on restatement. For control variables, all corporate governance variables are not significantly associated with restatement. On the other hand, Board of Commissioners independence, Audit Committee expertise, and institutional ownership are significantly associated with tax aggressiveness. As for company characteristics, size, leverage, growth rate, and profitability are not associated with restatement, but they are associated, except leverage, with tax aggressiveness.